Significance of AtMTM1 and AtMTM2 for Mitochondrial MnSOD Activation in Arabidopsis - Hu, Shu-Hsuan; Lin, Shu-Fan; Huang, Ya-Chen; Huang, Chien-Hsun; Kuo, Wen-Yu; Jinn, Tsung-Luo (Frontiers in Plant Science, 2021)
The Mn tracking factor for mitochondrial Mn superoxide dismutase (MnSOD) has been annotated as yMTM1 in yeast, which belongs to the mitochondrial carrier family. We confirmed that Arabidopsis AtMTM1 and AtMTM2 are functional homologs of yMYM1 as they can revive yeast MnSOD activity in yMTM1-mutant cells. Transient expression of AtMnSOD-3xFLAG in the AtMTM1 and AtMTM2-double mutant protoplasts confirmed that AtMTM1 and AtMTM2 are required for AtMnSOD activation. Our study revealed that AtMnSOD interacts with AtMTM1 and AtMTM2 in the mitochondria. The expression levels of AtMTM1, AtMTM2, and AtMnSOD corresponded positively with methyl viologen and metal stress. AtMTM1 and AtMTM2 are involved in Mn and Fe homeostasis, and the loss of AtMTM1 and AtMTM2 altered root length and flowering time. Transient expression of chloroplast-destined AtMnSOD revealed an evolutionarily conserved activation mechanism of chloroplastic-localised MnSOD in some algae still exists in Arabidopsis chloroplasts. This study strengthens the proposition that AtMTM1 and AtMTM2 respond to oxidative stress and participate in post-transcriptional AtMnSOD activity and ion homeostasis.